Pemberdayaan Masyarakat Desa Wisata Budaya Jonotemayang Bojonegoro Jawa Timur - Musyafa’ah, Nur Lailatul (LP2M of Institute for Research and Community Services - UIN Walisongo, 2017)
Jono Temayang Bojonegoro Village is known as a cultural tourism village. On January 20-February 19, 2016, 21 students of UIN Sunan Ampel Surabaya and a lecturer supervising the community in Jono Temayang Bojonegoro village in Real Work Participatory Action Research (KKN PAR). KKN PAR is implemented to optimize the empowerment of the community of cultural tourism village Jono Temayang Bojonegoro. Based on the results of mapping and transect, it is known that Jono village has tremendous potential to be developed from agriculture, animal husbandry, culture, religion and education. Among the problems faced by the Jono community are environmental, religious and educational issues. Based on the existing problems, then the action of the team accompanying the community is to establish a garbage bank, planting a toga plant, holding a